1993
DOI: 10.1002/rcm.1290070619
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of UV‐crosslinked protein–nucleic acid complexes by matrix‐assisted laser desorption lonization mass spectrometry

Abstract: Interactions between proteins and nucleic acids are important in the fundamental cellular processes that drive replication, recombination, dynamic alteration and repair of DNA, transcription and processing of RNA, synthesis of proteins, and regulation of enzyme activities. As part of an effort to develop a general, sensitive mass spectrometric strategy for the characterization of protein-nucleic acid interactions, we have used matrix-assisted laser desorption-ionization (MALDI) time-of-flight mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 14 publications
1
45
0
Order By: Relevance
“…To determine and sequence the oligoribonucleotides crosslinked to peptides in 30 S ribosomal subunits, we have successfully applied MALDI-MS. To date, similar studies using MALDI-MS have only been carried out on cross-linked protein-DNA complexes (36), but without oligonucleotide sequence determination.…”
Section: Discussionmentioning
confidence: 99%
“…To determine and sequence the oligoribonucleotides crosslinked to peptides in 30 S ribosomal subunits, we have successfully applied MALDI-MS. To date, similar studies using MALDI-MS have only been carried out on cross-linked protein-DNA complexes (36), but without oligonucleotide sequence determination.…”
Section: Discussionmentioning
confidence: 99%
“…In pioneering studies, Jensen et al [28] and Steen et al [29] demonstrated the mass spectrometric analysis of peptide-DNA oligonucleotides by matrix-assisted laser desorption/ionization (MALDI) and electrospray ionization (ESI), respectively. Other studies of protein-nucleic acid crosslinks using mass spectrometry followed [9, 10, 30 -33].…”
mentioning
confidence: 99%
“…Mass Spectrometry-MALDI mass spectrometry was performed by the Mass Spectrometry Facilities and Service Core Unit (Environmental Health Science Center, Oregon State University) using a custombuilt time of flight instrument (31). Two different matrices were used in the sample preparation: (i) 10 mg/ml of sinapinic acid dissolved in 33% acetonitrile and 67% trifluoroacetic acid (0.1% solution) was mixed (3:1) with samples (0.5 l) containing 10 M modified or unmodified Ugi protein; and (ii) a saturated solution of ␣-cyano-4-hydroxycinnamic acid in 33% acetonitrile and 67% trifluoroacetic acid (0.1% solution) was mixed (10:1) with samples (0.5 l) containing CNBr-treated Ugi, purified peptide C3, and Asp-N-digested Ugi protein.…”
Section: S]ugi or Edc/gee-modified [mentioning
confidence: 99%